The ICSID convention: a commentary a commentary on the Convention on the settlement of investment disputes between states and nationals of other states - Schreuer, Christoph 1944-; Malintoppi, Loretta 1956-; Reinisch, August 1965-; Sinclair, Anthony (Cambridge University Press, 2009)
This unique compendium offers an article-by-article commentary to the Convention on the Settlement of Investment Disputes between States and Nationals of Other States. Providing a comprehensive explanation of the functioning of this important mechanism for the settlement of investor–host State disputes, it incorporates the preparatory work, the Convention's text, various rules and regulations adopted under the Convention, the practice of arbitral tribunals under the Convention and academic writings on the subject. The first edition of this work has been relied upon by numerous arbitral tribunals. This second edition follows the same system and approach, but extensive updates reflect the vast increase in arbitral practice since the publication of the first edition. A number of novel issues that have emerged through this practice are now addressed, making this practice-oriented guide an indispensable tool for anyone dealing with the ICSID Convention
Keywords: International Centre for Settlement of Investment Disputes; Übereinkommen zur Beilegung von Investitionsstreitigkeiten zwischen Staaten und Angehörigen anderer Staaten -- 1965 März 18; Recht; Arbitration and award; Investments, Foreign / Law and legislation; Investitionsschutz; Völkerrecht; Verfahrensrecht; Investitionsstreitigkeit